Management of immune related adverse events induced by immune checkpoint inhibition - Teufel, Andreas; Zhan, Tianzuo; Härtel, Nicolai; Bornschein, Jan Alexander; Ebert, Matthias; Schulte, Nadine (Cancer letters, 2019)
In recent years, immune checkpoint inhibitors (ICIs) were successfully introduced to cancer therapy and these drugs have already become essential for the treatment of various non-curable tumors. Compared to conventional chemotherapy or tyrosine kinase inhibitors, ICIs generally exhibit a favorable side effect profile further promoting their increasing prescription rate. However, increasing use of these substance made clear that ICI induced activation of the immune system may also lead to immune-related adverse events (irAEs). Common irAEs are dermatological, gastrointestinal, or endocrine side effects but further tissue types and organ systems may also be affected. A detailed knowledge of these potential side effects is important as early recognition is the key to successful treatment, reversibility of organ dysfunction and in some cases even prevention of fatal outcome. In more severe irAEs, immunosuppression may be necessary to cope with these side effects. To increase awareness of irAEs and support immediate and successful management, we provide a comprehensive review on most common irAEs of ICIs, their diagnosis, and treatment.